1970
DOI: 10.1128/jb.104.3.1158-1167.1970
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Methicillin Resistance in Staphylococcus aureus Dependent on an Unusual Specificity of the Recipient Strain

Abstract: Resistance to methicillin was transduced by phage 80 or 53 from two naturally occurring methicillin-resistant strains of Staphylococcus aureus to methicillinsusceptible recipient strains at frequencies of 10-v to 10-9. Ultraviolet irradiation of transducing phage and posttransductional incubation at 30 C were essential for useful frequencies of transduction. Effectiveness as a recipient for this transduction was highly specific. Strain NCTC 8325 (PS47) in its native state was an ineffective recipient but becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
1

Year Published

1971
1971
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 27 publications
1
50
1
Order By: Relevance
“…Transfer of the SCCmec element via bacteriophages has not yet been proven, it is hypothesized that in particular the elements of size smaller than the S. aureus siphophage genome (45 kb), such as the SCCmec type I or type IV elements, can be transferred via generalized transduction. Experimental evidence for phage-mediated transduction of methicillin resistance by bacteriophages j80 and j53 from different naturally occurring MRSA strains to strain 8325 variants with low frequencies, which depended on the selected transducing systems had been described by Cohen and Sweeney (1970). Later, it was shown that this transduction is efficient only in recipient strains with a penicillinase plasmid (Cohen and Sweeney, 1973;Stewart and Rosenblum, 1980).…”
Section: Gene Locationmentioning
confidence: 99%
“…Transfer of the SCCmec element via bacteriophages has not yet been proven, it is hypothesized that in particular the elements of size smaller than the S. aureus siphophage genome (45 kb), such as the SCCmec type I or type IV elements, can be transferred via generalized transduction. Experimental evidence for phage-mediated transduction of methicillin resistance by bacteriophages j80 and j53 from different naturally occurring MRSA strains to strain 8325 variants with low frequencies, which depended on the selected transducing systems had been described by Cohen and Sweeney (1970). Later, it was shown that this transduction is efficient only in recipient strains with a penicillinase plasmid (Cohen and Sweeney, 1973;Stewart and Rosenblum, 1980).…”
Section: Gene Locationmentioning
confidence: 99%
“…The genetic locus of methicillin resistance is still uncertain. Transduction experiments with our strains have shown no linkage of this determinant with penicillinase plasmids (8). However, other workers, using different strains, have reported some co-transduction of methicillin resistance and penicillinase plasmids and have suggested that methicillin resistance may be plasmid-mediated (9,10).…”
mentioning
confidence: 51%
“…Organisms. The nomenclature and the designations of most of the organisms employed have been described (8,25). The methicillin-resistant S. aureus strain Dumas, originally described by Dornbusch et al (10), was obtained from S. J. Seligman.…”
Section: Methodsmentioning
confidence: 99%
“…We were also unable to transduce the mth marker into strains 62, 108, or 247. Cohen and Sweeney (6) have observed that transduction of mth is more likely to occur in S. aureus if the recipient strains contain penicillinase plasmids. For this reason, we tried to transduce mth into an additional 12 S. epidermidis strains which were penicillinase producers, although it was not known if these resistances were due to chromosomal or plasmid genes.…”
mentioning
confidence: 99%